The Effect Of Administering Liquid Organic Fertilizer Doses For Petai Cina On The Growth Of Water Spinach And Kailan Vegetable - Jegili, Yohanes Dwi Putra; Picauly, Intje; Laga Nur, Marselinus; Jutomo, Lewi (Pergizi Pangan DPD NTT, 2026)
Food availability is related to the sustainability of agriculture in drylands. Practical efforts to improve soil quality are through the application of organic fertilizer. The purpose of this study was to determine the effect of liquid fertilizer doses of Chinese Petai on the growth of Kale and Kailan vegetables. This study was conducted in July 2024-October 2025 on the land of Nusa Cendana University in the Food Ecology Project area. This study is a parametric study with a Complete Random Design (CRD) design consisting of four treatments with five replications. The sample of this study involved two types of plants, namely kale and kailan vegetables. Data were analyzed using ANOVA, then Honest Real Difference (HSD) analysis followed by Duncan Multiple Range Test (DMRT) at a significance level of 5%. The results of the analysis showed that the distribution of POC Chinese Petai has a very significant effect on the growth and development of Kale and Kailan. All plant growth parameters, leaf width and number of leaves showed a significant increase. Treatment P2: 10 tablespoons of POC (10 ml) / 5 L of water has the best effect on stem height, leaf width and number of Kale and Kailan leaves significantly different from treatment P0: Control (water), P1: 5 tablespoons of POC (5 ml) / 5 L of water, P3: 15 tablespoons (15 ml) / 5 L of water. POC Petai china is expected to be an alternative in limited organic fertilizer to support family and community food security factors.